DESIGN AND DEVELOPMENT OF LOW HP TRACTOR DRAWN INCLINED PLATE GROUNDNUT PLANTER - K.MADHUSUDHANA REDDY, D.VIJAY KUMAR, B.SAHADEVA REDDY and M.V.RAMANA (The Journal of Research ANGRAU, 2023)
In Andhra Pradesh, groundnut is one of the major oil seed crop grown in an area of 9.0 lakh ha annually under rainfedconditions in red soils. High HP tractor drawn groundnut planters can be used for sowing of groundnut but large initial investment of high HP tractors may not permit for using by small and medium farmers. As a consequence, the small and medium farmers are turning towards low HP tractors, which are less expensive, compared to high HP tractors. However, the planting the implements are not widely available that are suitable to low HP tractors and local soil conditions. Keeping this in-view, a low HP tractor drawn 4-row groundnut planter was developed and evaluated its performance. Row to row spacing of groundnut planter is 30cm. The seed metering in the planter is of inclined plate type. Power is transmitted from ground wheel to metering system through chain and sprockets with power transmission ratio of 1.41. A double point shovel type furrow opener was provided for opening the furrows. The seed is placed in the furrows at desired depth of 4.5 cm and sees to seed spacing of 10.1 cm. The implement can operated by a 18 - 24 HP tractor. During evaluation the field capacity of the planter was found to be 0.24 ha h-1 at the average speed of operation of 2.88 km h-1 with field efficiency of 69.44%. It was found that, the cost of sowing with low HP tractor drawn groundnut planter was Rs.1,085/- per ha.